Теоретичні основи процесів інерційно-фільтруючої сепарації - Ляпощенко, Олександр Олександрович (Національний університет "Львівська політехніка", 2016)
Дисертація являє собою теоретичне узагальнення результатів досліджень автора і присвячена вирішенню актуальної науково-прикладної проблеми, сутність якої полягає в створенні теоретичних основ процесів інерційно-фільтруючої сепарації і науково обґрунтованих методів розрахунку основних технологічних параметрів та характеристик інерційно-фільтруючих сепараційних пристроїв, в яких поєднані принципи одночасної взаємодії інерційних та фільтруючих сепараційних елементів, чим досягається зниження гідравлічного опору та підвищення ефективності сепарації у широких діапазонах навантажень та співвідношення фаз. Аналітично та чисельно розв’язано системи рівнянь руху і нерозривності газового потоку для окремого випадку плоского плину в криволінійному каналі, рівнянь руху дисперсних часток (краплин) в турбулентному газодисперсному потоці, ламінарного руху вловленої рідини в плівці, що стікає по стінках каналу та в шарі волокнистого фільтру, виходячи з умов усталеного руху та рівноваги (балансу сил) на міжфазній поверхні, що визначають особливості взаємодії плівки сепарованої рідини з газовим потоком в криволінійних інерційно-фільтруючих сепараційних каналах, чим закладено теоретичні основи теорії інерційно-фільтруючої сепарації. Розвинута континуальна модель криволінійної течії газодисперсного потоку дозволяє розрахунковим методом визначити траєкторії руху дисперсних часток, розподіл їх по розмірах і відповідно здійснити оптимізаційне геометричне профілювання криволінійних каналів, визначити зони доцільного розташування, форму та розміри фільтруючих елементів, оцінити ефективність сепарації після кожної послідовної криволінійної ділянки (ступеня сепарації) інерційно-фільтруючого сепараційного каналу. Диссертация представляет собой теоретическое обобщение результатов исследований автора и посвящена решению актуальной научно-прикладной проблемы, суть которой заключается в создании теоретических основ процессов инерционно-фильтрующей сепарации и научно обоснованных методов расчета основных технологических параметров и характеристик инерционно-фильтрующих сепарационных устройств, в которых объединены принципы одновременного взаимодействия инерционных и фильтрующих сепарационных элементов, чем достигается снижение гидравлического сопротивления и повышение эффективности сепарации в широких диапазонах нагрузок и соотношения фаз. Аналитически и численно решены системы уравнений движения и неразрывности газового потока для отдельного случая плоского течения в криволинейном канале, уравнений движения дисперсных частиц (капель) в турбулентном газодисперсном потоке, ламинарного движения уловленной жидкости в стекающей пленке по стенкам канала и в слое волокнистого фильтра, исходя из условий установившегося (стационарного) движения и равновесия (баланса сил) на межфазной поверхности, которые определяют особенности взаимодействия пленки сепарированной жидкости с газовым потоком в криволинейных инерционно-фильтрующих сепарационных каналах, чем заложены теоретические основы теории инерционно-фильтрующей сепарации. Получившая развитие континуальна модель криволинейного течения газодисперсного потока позволяет расчетным методом определить траектории движения дисперсных частиц, распределение их по размерам и соответственно осуществить оптимизационное геометрическое профилирование криволинейных каналов, определить зоны рационального расположения, форму и размеры фильтрующих элементов, прогнозировать эффективность сепарации после каждого последовательного криволинейного участка (ступени сепарации) инерционно-фильтрующего сепарационного канала. The thesis represents a theoretical generalization of author’s results of research and is devoted to solving an urgent scientific and applied problem that concerns the creation of theoretical foundations of processes of the inertial-filtering separation, as well as science-based methods of calculating the basic technological parameters and characteristics of the inertial-filtering separation devices, which combine the principles of simultaneous interaction of inertial and filtering separation elements. Thus, the reduction of hydraulic resistance and rising the separation efficiency in a wide range of loads and phases relation are achieved. The perspective directions of the organization of motion and interaction of two-phase flows are defined. It has led to the invention of new ways of the inertial-filtering separation and development of a new separate class of the inertial-filtering separation devices, for which the basic laws of processes of gravitational and inertial settling, as well as trapping the dispersed particles are determined by filtration mechanisms on filter fibers and trapped liquids in the curvilinear inertial-filtering separation channels. The task of the analytical and numerical solution of mathematical models from the system of motion equations has been solved, as well as the equation of continuity of a gas stream for a special case of the flat flow in the curvilinear channel, equations of motion of dispersible particles (droplets) in the turbulent gas-dispersion flow, laminar motion of trapped liquids in the film that flows on the wall of the channel and in the layer of fibrous filter, based on the conditions of steady motion and equilibrium (force balance) on the boundary surface, define features of the interaction of film separated liquids film with a gas stream in the curvilinear inertial-filtering separation channels, than the theoretical foundation of the theory of the inertial-filtering separation. The developed continual model of curved gas-dispersion flow allows using a calculation method to determine the motion trajectory of dispersible particles, their distribution by the sizes and therefore to carry out an optimization geometric profiling of curvilinear channel, as well as to determine the efficient location zones, form and sizes of filtering elements and to estimate the effectiveness of separation after each serial curvilinear areas (degree of separation) of inertial-filtering separation channel. The problem of the analysis of coupled interphase heat and mass transfer influence on the processes of the inertial-filtering separation of multicomponent gas-condensate mixtures are considered and obtained the further development of the physical model of formation and phase equilibrium of the highly refined gas and condensate system in the turbulent gas flow that includes the effect of phase transformation and drop coalescence of condensed fluid on the efficiency of processes of inertial-filtration separation with condensation. The scientifically based practical recommendations for the design and engineering methods for calculating the gas-dynamic separators for the purpose to enhance separation efficiency and reduce the hydraulic resistance with determination of the optimal design parameters of inertial-filtering separation elements are developed. The program and technique of experimental-industrial testing new inertial-filtering separators and separation unit blocks are developed. According to the results of research and proofing of exposed and experimental-industrial testing the inertial-filtering separators, their main hydraulic and separation indicators are determined that confirmed the high technical characteristics of the proposed equipment. The received scientific results in dissertation work and practical recommendations are implemented in production at the engineering plants, chemical industry enterprises, as well as oil and gas industry.
Теоретические основы процессов инерционно-фильтрующей сепарации
Theoretical foundations of the processes of inertial-filtering separation
Keywords: теоретичні основи; гідромеханічні процеси; механізми інерційно-фільтруючої сепарації; гідравлічний опір; ефективність сепарації; теоретические основы; гидромеханические процессы; механизмы инерционно-фильтрующей сепарации; гидравлическое сопротивление; эффективность сепарации; theoretical foundations; hydromechanical processes; mechanisms of inertial-filtering separation; hydraulic resistance; efficiency of separation